Canadian mapping of autism-specific supports for postsecondary students. (February 2022) - Ames, Megan E.; Coombs, Courtney E.M.; Duerksen, Kari N.; Vincent, Jonathan; McMorris, Carly A.
Highlights: Only 15 (6%) Canadian postsecondary institutions provide autism-specific supports. The most common support is providing information on the institution's website. Supports were more commonly identified among universities and in Central Canada. Abstract: Background: Many autistic students have a variety of strengths and the desire to succeed in postsecondary education. Nonetheless, most autistic students report not receiving adequate support in postsecondary education to ensure their success. Students also report difficulty in navigating complex institutional systems. We conducted an environmental scan of autism-specific supports (e.g., website information, transition programs, peer mentoring) available to autistic students within Canada's publicly-funded postsecondary institutions. We also examined distribution of autism-specific supports across institutional type (i.e., university, junior college, technical/vocational) and geographic region. Method: A Boolean search strategy was used to collect data from institutional websites. Results: Of the 258 publicly-funded postsecondary institutions in Canada, only 15 institutions (6%) had at least one support. Of the 15 institutions identified, the most common autism-specific support included information on the institution's website (67%), followed by transition to university support (47%), social group(s) (33%), peer mentoring (27%), specialist tutoring and support with daily living (20%), transition to employment support (13%), and student-led societies and autistic student advocate (7%). In general, universities and institutions in Central Canada (i.e., Ontario) had a disproportionate number of provisions. Conclusions: There are promising advances with respect to autism-specific supports in postsecondary institutions across Canada. We recommend further research to better understand how students access these supports and more comprehensive evaluations of such supports, specifically informed by collaborations with autistic students.